The impact of the ageing Italian population on the labour market - Krasavina, Polina (2024)
Italy's ageing population, caused by a constantly declining birth rate and increasing life expectancy, raises concerns for its labour market. This master's thesis explores how this demographic shift will impact workforce participation, productivity, wage formation, skill gaps, and new labour market opportunities. The research analyzes possible measures and policy options to address current issues, including promoting later retirement, attracting more women and youth to the labour market, navigating immigration, reconsidering the Active Ageing policy, and propagating the importance of lifelong learning and intergenerational collaboration.